Competitiveness and External Trade Performance of the French Manufacturing Industry - Agenor, Pierre-Richard. (Washington, D.C. : International Monetary Fund, 1995)
This paper provides an assessment of competitiveness and external trade performance of the French manufacturing industry during the 1980s and early 1990s. The first part of the paper reviews developments in a broad range of competitiveness indicators. The analysis indicates that the manufacturing sector appears to have maintained its competitive position in recent years. The second part discusses developments in export market shares. The third part estimates a vector error correction model relating the trade ratio to relative unit labor costs, domestic and foreign demand, and nonprice competitiveness. Variance decompositions suggest that fluctuations in price and nonprice competitiveness account for about two-fifths of fluctuations in manufacturing trade flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet